Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/pharmaceutics11100544
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Prediction of Ibuprofen Release from 3D DLP Printlets Using Artificial Neural Networks

Abstract: The aim of this work was to investigate effects of the formulation factors on tablet printability as well as to optimize and predict extended drug release from cross-linked polymeric ibuprofen printlets using an artificial neural network (ANN). Printlets were printed using digital light processing (DLP) technology from formulations containing polyethylene glycol diacrylate, polyethylene glycol, and water in concentrations according to D-optimal mixture design and 0.1% w/w riboflavin and 5% w/w ibuprofen. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…So far, PEGDA 575, without the addition of any excipients or with addition of PEG 300, was used for printing polypills containing: paracetamol, naproxen, caffeine, aspirin, prednisolone, and chloramphenicol [ 15 ], while PEGDA 400 was used for printing tablets containing theophylline as active substance. Paracetamol [ 11 , 16 ], 4-aminosalicylic acid [ 11 ] and ibuprofen [ 35 , 47 ], were used as active substances in photopolymerization based printing processes, combined with a mixture of PEGDA and PEGs of different molecular weights. In our study, tablets containing four different amounts of ATH suspended in PEGDA/PEG 400 mixture were successfully produced by the DLP printer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, PEGDA 575, without the addition of any excipients or with addition of PEG 300, was used for printing polypills containing: paracetamol, naproxen, caffeine, aspirin, prednisolone, and chloramphenicol [ 15 ], while PEGDA 400 was used for printing tablets containing theophylline as active substance. Paracetamol [ 11 , 16 ], 4-aminosalicylic acid [ 11 ] and ibuprofen [ 35 , 47 ], were used as active substances in photopolymerization based printing processes, combined with a mixture of PEGDA and PEGs of different molecular weights. In our study, tablets containing four different amounts of ATH suspended in PEGDA/PEG 400 mixture were successfully produced by the DLP printer.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of using the DLP printer here demonstrated are the possibility of customization of the printing parameters depending on the formulation factors, fast printing of pharmaceutical dosage forms, as well as printing at room temperature. Previous studies based on DLP 3D printing have also shown these possibilities as potential advantages of this technology [ 12 , 16 , 35 ]. In comparison with other 3D printing technologies investigated for tablet production, DLP has a limited number of photopolymers suitable for pharmaceutical use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a digitally controlled printing head emits light to selective points of a building platform immersed in uncured resin, forming consecutive layers of newly cured solid polymer (10). The two most common forms of photopolymerisation are stereolithography (SLA) and digital light processing (DLP), with various examples of their applications available in the literature (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The drug release predicted with STATISTICA 7.0 was quite similar to the one obtained experimentally. This study described that suitable ANN allows to recognise the input-output relationship in DLP printing of pharmaceutics [16].…”
Section: Digital Light Processing (Dlp)mentioning
confidence: 99%